Model Pembelajaran Praktik Pengayaan Motor Listrik Arus Searah Berbantuan Program Delphi - Istanto Wahyu Djatmiko; Sunyoto Sunyoto; Deny Budi Hertanto (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
This study aims to determine the quality of the direct current electric motor enrichment practice learning media utilizing the Delphi program, the effectiveness of the media, and the enrichment practice learning model utilizing the Delphi program. This study was categorized as a research and development. The subjects of the study were 15 students of the Electrical Engineering department in Engineering Faculty of Yogyakarta State University. The data was analysed descriptively and described in frequency distribution categories. The results of the study were: (1) the quality of the developed materials and the quality of the developed media were categorized as very good and good respectively (2) the effectiveness of the materials was categorized as good (3) the applicable procedure of the developed learning media for the students